Phycocyanin Additives Regulate Bacterial Community Structure and Antioxidant Activity of Alfalfa Silage - Xiangdong Liu; Yichao Liu; Mingjian Liu; Jing Xing; Yuxuan Wang; Panjie Sheng; Gentu Ge; Yushan Jia; Zhijun Wang (Microorganisms)
Phycocyanin is a water-soluble pigment protein extracted from prokaryotes such as cyanobacteria and has strong antioxidant activity. As a silage additive, it is expected to enhance the antioxidant activity and fermentation quality of alfalfa silage. This study revealed the effects of different proportions of phycocyanin (1%, 3%, 5%) on the quality, bacterial community and antioxidant capacity of alfalfa silage. The results showed that 5% phycocyanin supplementation could maintain dry matter (DM), crude protein (CP) and water-soluble carbohydrate (WSC) content; increase lactic acid (LA) content; decrease pH and butyric acid (BA) and ammonia nitrogen (NH3-N) content; and improve fermentation quality. At the same time, the contents of total antioxidant capacity (TAOC), total phenol content (TP), polysaccharide content (P) and total flavonoid content (F) in the addition group were significantly increased, the antioxidant capacity was enhanced and the abundance of lactic acid bacteria was increased, which was positively correlated with silage quality. Phycocyanin can improve the metabolic function of carbohydrates and amino acids and promote the production of secondary metabolites. The application of phycocyanin broadens the variety of additives for alfalfa silage.